Formation of massive seed black holes via collisions and accretion - Boekholt, Tjarda; Schleicher, D. R. G.; Fellhauer, M.; Klessen, Ralf S.; Reinoso, B.; Stutz, A. M.; Haemmerlé, L. (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. Models aiming to explain the formation of massive black hole seeds, and in particular the direct collapse scenario, face substantial difficulties. Th